Quadric Surface Extraction by Variational Shape Approximation - Yan, Dong-Ming; Liu, Yang; Wang, Wenping (Geometric Modeling and Processing - GMP 2006: 4th International Conference, 2006)
Based on Lloyd iteration, we present a variational method for extracting general quadric surfaces from a 3D mesh surface. This work extends the previous variational methods that extract only planes or special types of quadrics, i.e., spheres and circular cylinders. Instead of using the exact L2 error metric, we use a new approximate L2 error metric to make our method more efficient for computing with general quadrics. Furthermore, a method based on graph cut is proposed to smooth irregular boundary curves between segmented regions, which greatly improves the final results.